Peran Mahasiswa MSIB Batch 5 Divisi Marketing Communication Education Content terhadap Database Marketing - Ananta, Kalyana Risma (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
This report details the execution of MSIB activities undertaken by the author as the final Internship Report at PT Maleo Edukasi Teknologi for approximately 5 months, from August 14th to December 31st, 2023. The internship program at PT Maleo Edukasi Teknologi (Educourse.id) accommodated a total of 100 participants. Educourse.id functions as a subsidiary of PT Maleo Edukasi Teknologi, established on June 1st, 2020, with a vision to become the foremost STEAM-based educational learning platform preparing future skills aligned with Indonesia's Industry 4.0. Focused on STEM education, Educourse.id's report encompasses the implementation of the marketing communication education content division at Educourse.id, outlining the processes, obstacles encountered, and successes achieved in marketing Educourse.id's products.